Detection and prediction ofStreptococcus pneumoniaeserotypes directly from nasopharyngeal swabs using PCR. Issue 8 (August 2015) - Lang, Amanda L. S.; McNeil, Shelly A.; Hatchette, Todd F.; Elsherif, May; Martin, Irene; LeBlanc, Jason J.
Abstract : N/A: Monitoring Streptococcus pneumoniae serotype distribution is important to assess the impact and effectiveness of pneumococcal vaccine programs. With the challenges of Quellung serotyping, PCR‐based serotype prediction is increasingly being used for large‐scale epidemiological studies. This study used real‐time (RT)‐PCR targeting the genes encoding autolysin ( lytA ) and capsular biosynthesis gene A ( cpsA ) of S. pneumoniae in nucleic acids extracted directly from nasopharyngeal (NP) swabs submitted for viral studies. If the specimen was lytA or cpsA PCR‐positive, then serotype prediction was performed on the same nucleic acid using eight conventional multiplex PCRs (cmPCRs) and seven real‐time multiplex PCRs (rmPCRs). Of 1770 NP swabs, 132 (7.5 %) were lytA ‐positive and 122 (6.9 %) were positive for both targets ( lytA and cpsA ). Of the 122 lytA + cpsA + specimens, a serotype could be assigned in 52 (41.8 %) using cmPCR alone and the yield was increased to 70 (57.4 %) with the addition of rmPCR. Based on sensitivity, incremental yield and more efficient workflow, an algorithm was proposed where lytA and cpsA RT‐PCR screening was followed by serotype deduction using rmPCR and a modified set of four instead of eight cmPCRs. This algorithm was validated for use on NP swabs, and the distribution of S. pneumoniae serotypes deduced from this approach showed good concordance with those obtained with cultured isolates serotyped by Quellung and PCR. Overall, molecular detection and serotyping of S. pneumoniae from NP swabs was found to be a valuable tool to assess S. pneumoniae colonization and monitor trends in serotype distribution.